(3ahGFO CHj GdbGSe GdMSjf Hf eMeO Hf EHQGgje GdMfGFis - (3YHO GdYRjR Hf eMeO Hf eMeO Hf YGUe GdfNTHjs ((3fLe GdOjf YeQ Hf eMeO Hf agO GdgGTei s)
(3ChdgG (B:s
(3MOKfG CHh GdMSjf YHO GdhgGH Hf GdLQjQ GdhdjO Hf ehSi Hf QGTO GdcdGfi s
(3BNQgG (B:s
(3Cgd GdbHhQ dGf JWGhd fhHce adJYbHf ZOkG HWhd bjGe BNQ GdLRA GdKGf ef ahGFO GdTjN GdEeGe GdLfGFi , JNQjL GdfNTHi s
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW eged GdfbW CMjGfkGs
(3HBNQgG SeGYGJ YOI CbOegG SeGY SfI (B520 (3hSfI (B525 s
(3JHUQI GdYfhGf (B:s
(3JNQjL s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs